Sclerosing angiomatoid nodular transformation of the spleen. Issue 10 (10th September 2015) - Murthy, Vidhya; Miller, Ben; Nikolousis, Emmanuel M.; Pratt, Guy; Rudzki, Zbigniew
Key Clinical Message Sclerosing angiomatoid nodular transformation (SANT) of spleen is a very rare benign entity with unknown etiology. Here, we report this unusual case in a fit middle‐aged gentleman and discuss various diagnostic modalities along with the management of this condition.